PENGARUH MANAJEMEN TERKOOPTASI, RASIO PROFITABILITAS DAN ASET TETAP TERHADAP TAX AVOIDANCE - Setiadi Alim Lim (Jurnal Akuntansi dan Pajak, 2026)
Abstract Tax evasion and tax avoidance are common phenomena that occur when taxpayers fulfill their tax obligations to the government, essentially attempting to minimize the amount of tax paid. The difference is that tax evasion is declared illegal, while tax avoidance is categorized as legal. Recently, the term "co-opted directors" has emerged, which refers to directors appointed while the CEO (Chief Executive Officer) is still in office. These co-opted directors' independence in carrying out their control and oversight duties over the CEO is questionable, despite their formal designation as independent directors. This study examines the influence of co-opted directors, co-opted commissioners, profitability, and property, plant, and equipment on tax avoidance. This research is categorized as quantitative and aims to test the developed hypotheses. The population of the study is all pharmaceutical companies listed on the Indonesia Stock Exchange (IDX). The sampling method used for sampling is non-probability purposive sampling. The sample obtained is 10 companies. The research data is secondary data taken from the company's financial statements for the period 2013-2024 (12 years). Multiple linear regression was used to analyze the data. The results of the study indicate that simultaneously (F test) all independent variables, namely co-opted directors, co-opted commissioners, profitability, and property, plant, and equipment, have an effect on the dependent variable of tax avoidance. When a partial analysis was conducted (t test), only the variables of profitability and property, plant, and equipment had an effect on the tax avoidance variable, while the variables of co-opted directors and co-opted commissioners had no effect on the tax avoidance variable. The results of this study support several other research findings, but also contradict the results of other studies.